Stability Analysis of LCC-HVDC with PV Station at the Receiving End - Yuqing ZHOU; Dahu LI; Wei YAO; Qihang ZONG; Hongyu ZHOU; Jinyu WEN (Zhongguo dianli)
A new type of receiving-end power system with high proportion of new energy and HVDC has been formed in Hubei. In the scenario where the PV station is located near the HVDC receiving-end converter station, the sub-synchronous oscillation characteristics of power electronic devices and the interactions between the sub-systems are still to be analyzed. This paper used eigenvalue analysis method to explore the influence of the massive infeed of PV stations. Firstly, with a small signal analysis model of HVDC with PV station established, this paper has confirmed that the infeed of PV stations has a significant influence on the system stability. The interaction characteristics between subsystems were further observed through the dominant mode, and the feasible region of photovoltaic control parameters set, with a view to lower risks of sub-synchronous oscillation in the system. Finally, this paper defined the subsystem participation degree and measured the influence of operational parameters on the sub-synchronous interaction between the systems. It is concluded that the interaction between the PV plant and the DC system is stronger in the case of low grid strength and high light intensity at the receiving end. When designing a PV plant for grid connection, a conductor with a small impedance ratio should be selected to reduce the distance of the PV grid connection line. This conclusion can provide a theoretical basis for photovoltaic grid-connected design.